2013
DOI: 10.1111/jopr.12105
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Antimicrobial Macromolecules in Acrylic Denture Base Resins: A Research Composition and Update

Abstract: Contemporary research in acrylic denture base materials focuses on the development of a novel poly(methyl methacrylate) (PMMA) resin with antimicrobial properties. Although PMMA resin has fulfilled all the requirements of an ideal denture base material, its susceptibility to microbial colonization in the oral environment is a formidable concern to clinicians. Many mechanisms including the absence of ionic charge in the methyl methacrylate resins, hydrophobic interactions, electrostatic interactions, and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 77 publications
1
48
0
9
Order By: Relevance
“…Such an addition may reduce biofilm retention and promote the maintenance of a clean environment. A successful antimicrobial should represent a significant advance in the prevention of pathologies and improve the quality of life of patients with prosthetic devices, representing an advance with great clinical relevance …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an addition may reduce biofilm retention and promote the maintenance of a clean environment. A successful antimicrobial should represent a significant advance in the prevention of pathologies and improve the quality of life of patients with prosthetic devices, representing an advance with great clinical relevance …”
Section: Introductionmentioning
confidence: 99%
“…A successful antimicrobial should represent a significant advance in the prevention of pathologies and improve the quality of life of patients with prosthetic devices, representing an advance with great clinical relevance. 5,6 Nanotechnology, a science of the understanding and control of matter at the nanometre scale (between 1 and 100 nm), has attracted interest for improving the biological properties of dental materials. 7 Nanoscale materials demonstrate inherent characteristics that confer the ability to penetrate biological membranes such as the cell walls of bacteria, increasing the bactericidal effects.…”
mentioning
confidence: 99%
“…5 Despite the material's components of 3DR being similar to AR (Table 1), there are differences regarding the components of 3DR and the photoinitiators and the different degree of material conversion that could lead to different mechanical proprieties. 6,7,8,9…”
Section: Introductionmentioning
confidence: 99%
“…Uchimaru et al 24 reported that TiO 2 , which is a stable photocatalyst, combined with a tissue conditioner exhibited antimicrobial activity against Escherichia coli, S. mutans, and S. aureus, and antifungal activity against C. albicans. TiO 2 exhibits strong oxidizing power under UV radiation (from sunlight or an illuminated light source) 36 but no photocatalystic effects at nonradiation, 37,38 which means soft liners with TiO 2 may have no antifungal effect in the oral cavity environment. 38 When dentures are removed, for instance during sleep, the photocatalystic agents can allow for the maintenance of soft liners by radiation alone.…”
mentioning
confidence: 99%